POSTGRADUATE EDUCATION OF THE SECURITY SERVICE EMPLOYEES OF UKRAINE: STATE AND PROSPECTS OF IMPROVEMENT - Артюшин, Г. М. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2013)
The article is devoted to the problem of justifying the theoretical and methodological foundations of the retraining system and advanced training of the SBU. Induced experimental results on website devoted to the analysis of status and trends of retraining and advanced training of employees of the Security Service of Ukraine, the disclosure of research and testing ways of its further improvement